Océanographie, distribution et cycle annuel de la morue arctique (Boreogadus saida) en mer de Beaufort : une approche hydroacoustique - Benoit, Delphine (Université Laval, 2012)
Distribution and abundance of fish are greatly determined by trophic interactions and environmental conditions. Climate change in the Arctic constitutes major environmental modifications likely to influence the success of species. Within the pelagic trophic web of the Canadian Arctic, Arctic cod (Boreogadus saida) makes the most part of carbon fluxes between zooplanktonic production and top predators. However, the ecology of adult stages of this key species remains poorly known. This lack of knowledge is mostly attributable to sampling difficulties in the extreme conditions of the Arctic Ocean. Marine acoustics were used in this thesis, coupled with physical and biological oceanographic data, in order to improve the knowledge about Arctic cod’s ecology in the Beaufort Sea. A winter time series collected at 230 m deep fixed station in Franklin Bay enabled to uncover winter ecology of Arctic cod. The seasonal scale study showed that under the sea-ice cover, Arctic cod maintained in the lower half of the water column, and was associated with Pacific halocline. Biomass estimates progressively increased from late January (10 g m–3) to reach maximum values in April (2673 g m–3). This Arctic cod accumulation probably resulted from a passive advection within slope waters. The daily scale study revealed the existence of diel vertical migrations of Arctic cod, triggered by the rate of change in light intensity. The nocturnal migration of a part of the population toward surface reflects a behaviour adopted by smaller individuals to feed, reducing at the same time competition with larger individuals and predation by seals. Finally, the study of spatial distribution prior to sea-ice consolidation showed that Arctic cod concentrated on slopes (isobaths 150 to 600 m) of Mackenzie shelf and Amundsen Gulf. Densities were lower (< 1 g m –3) than in the winter aggregation and likely constituted the source for the aggregation detected in Franklin Bay. This thesis enabled to characterize the habitat of Arctic cod and trophic ...